Product Safety: Liability, R&D, and Signaling - Daughety, Andrew F.; Reinganum, Jennifer F. (American Economic Review, 1995)
We develop a monopoly model of product design and safety signaling incorporating a parametric liability specification. The firm first engages in R&D to affect the safety of its product. Since the outcome of R&D trials is unobservable to consumers, the firm then chooses its price, understanding that consumers may draw inferences from the price about the product's safety. Consumers acquire and use the product; injuries lead to losses which are allocated by the liability system. We vary the liability system's allocation of losses and trace out the implications for R&D investment and the price-safety relationship.